2021
DOI: 10.3389/fphar.2021.688227
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Gene Signatures using Next-Generation Sequencing Data from COVID-19 Infection Models: Focus on Neuro-COVID and Potential Therapeutics

Abstract: SARS-CoV-2 is the causative agent for coronavirus disease-19 (COVID-19) and belongs to the family Coronaviridae that causes sickness varying from the common cold to more severe illnesses such as severe acute respiratory syndrome, sudden stroke, neurological complications (Neuro-COVID), multiple organ failure, and mortality in some patients. The gene expression profiles of COVID-19 infection models can be used to decipher potential therapeutics for COVID-19 and related pathologies, such as Neuro-COVID. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 74 publications
2
16
0
Order By: Relevance
“…Lastly, for NHBE cell line, we saw molecular functions such as small molecule binding, carbohydrate derivative binding, etc. as shown in previous works ( 34 , 35 ). In stark contrast, for top 100 DEGs, only one statistically significant molecular function was enriched across all cell lines, namely, “sequence specific DNA binding function” in the Vero cell line.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Lastly, for NHBE cell line, we saw molecular functions such as small molecule binding, carbohydrate derivative binding, etc. as shown in previous works ( 34 , 35 ). In stark contrast, for top 100 DEGs, only one statistically significant molecular function was enriched across all cell lines, namely, “sequence specific DNA binding function” in the Vero cell line.…”
Section: Resultssupporting
confidence: 84%
“…Lastly, for NHBE cell line, we saw molecular functions such as small molecule binding, carbohydrate derivative binding, etc. as shown in previous works (34,35).…”
Section: Overview Of the Approachsupporting
confidence: 79%
“…Additionally, some of the purple module hub-high traffic genes, such as MAPK1 ( 189 , 374 ), CUL2 ( 210 ), CMTM6 ( 162 ), TXNRD1 ( 375 ), RAB1A ( 376 ), DICER1 ( 377 ), RAB5A ( 209 ), HSP90B1 ( 343 ), MAGT1 ( 378 ), ADAM10 ( 379 , 380 ), SNX2 ( 89 ), OLA1 ( 381 ), SPTLC1 ( 382 ), SH3GLB1 ( 383 ), TIMM10B ( 384 ), and CREB1 ( 385 ) hub-high traffic TF, which are central for information exchange in this module, are potential targets for development of COVID-19 therapeutic strategies. Among these, the mitogen-activated protein kinase 1 ( MAPK1 ) hub-high traffic gene is a potential core target for many anti-COVID-19 therapeutic strategies ( 189 , 374 , 386 390 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that natural products such as albiziasaponin-A, iso-orientin, and salvadorin can ameliorate the pathologies associated with AD in vivo ( Rasool et al, 2018 ) and that the natural products could be useful for the treatment of age-related degenerative diseases ( Kalamegam et al, 2020 ). In addition, we have recently shown that NGKD platforms can be successfully used to find drugs and natural products that may reverse disease-specific gene signatures ( Pushparaj et al, 2021 ). Therefore, NGKD platforms can be used to find drugs and natural products that can potentially reverse AD-associated gene signatures in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Trichostatin A increased the antioxidant capacity and cell viability of SH -SY5Y cells by enhancing Keap1-mediated inhibition of the Nrf2 pathway, thereby reducing amyloid-β peptide-mediated cell damage ( Li et al, 2020 ). Importantly, we recently predicted the potential of withaferin A, narciclasine, and trichostatin A to reverse gene signatures in neuro- COVID ( Pushparaj et al, 2021 ). However, the effects of natural products such as emetine, cephaeline, narciclasine, withaferin A, trichostatin A and drugs such as DMARDs and dasatinib which may be able to reverse AD gene signatures in astrocytes should be validated with appropriate experimental models from AD before being used for further clinical testing.…”
Section: Discussionmentioning
confidence: 99%